Mitra Tours & Travel, Kuala Lumpur / Siti Sara Salimi - Salimi, Siti Sara (Faculty of Hotel and Tourism Management, 2017)
Mitra Malaysia is owned and founded by Y.M Tunku Dato’ Seri Iskandar bin Tunku Tan Sri ‘Abdu'llah, a royal patron from the Negeri Sembilan monarch. The eldest son of the renowned socialite businessman who founded the Melewar Group dives through the similar footsteps of his late father into the swamps of business pools. He is currently siting on the board of directors of not only one megacorporation from a single line of production, Tunku Iskandar’s influential landed him as one of the board of directors of Mycron Steel Berhad, Melewar Group Berhad, and many more, as well as founding Mitra Malaysia Sdn. Bhd. (Mitra Tours & Travel and Mitra Kembara) Tunku Iskandar also actively strung his power on the Board of Malaysian Tourism Promotion, being Malaysia’s representative as ASEANTA Honorary Member.